Tourists' Perception Of The Impact Of Reviewers and Social Media On The Selection Of Cristine Hakim Idea Park Destinations - Rasyada, Amrina; Rizki, Nazyra Atika; Mardatila, Ayunin; Febriansyah, Febriansyah; Saputra, Yogiardi; Erningsih, Erningsih; Isnaini, Isnaini (Journal of Humanity Studies, 2024)
This study explores tourists' perceptions of the impact of reviews and social media in destination selection, focusing on experiences at Chip (Cristine Hakim Idea Park). Through a qualitative approach and in-depth interviews with 20 respondents, findings indicate that reviews and social media content play a crucial role in tourists' decision-making, influencing their perceptions of destination quality and attractiveness. Thematic analysis identifies patterns in these perceptions.destinations The research employs a qualitative approach with in-depth interviews as the data collection technique. Twenty respondents were purposively selected who had visited Chip (Cristine Hakim Idea Park) to provide rich insights into their experiences. Interviews focused on their perceptions of online reviews and the influence of social media in choosing tourist destinations. Data analysis is conducted using a thematic analysis approach, enabling researchers to identify patterns in tourists' perceptions of reviews and social media. With this approach, researchers can deeply understand how reviews and social media influence tourists' perceptions of specific tourist destinations.